PENGARUH BIODEGRADASI DENGAN TEKNIK PENANAMAN TERHADAP PRODUK LATEKS KARET ALAM BERPENGISI TEPUNG KULIT PISANG YANG DIPUTIHKAN DENGAN HIDROGEN PEROKSIDA - Erick Kamil; Emelya Khoesoema; Hamidah Harahap (Talenta Publisher (Universitas Sumatera Utara), 2012)
Natural rubber latex products filled with bleached banana skin powder were identified by burying samples in soil. Soil burial was carried out by adding NPK fertilizer and without fertilizer. One of the tests which was carried out was weight loss calculation. Weight loss calculation showed that natural rubber latex products filled with bleached banana skin powder biodegraded faster than natural rubber latex products without filler. The addition of fertilizer also contributed to biodegradability of samples. The other test was FTIR (Fourier Transform Infrared Spectroscopy) test. The results of FTIR test showed there were structure changes in natural rubber latex which indicated natural rubber latex had been biodegraded.